Life cycle and morphological identification of Globodera spp. related to potato (Solanum tuberosum L.) phenology in Nariño, Colombia - Betancourth, Carlos Arturo; Moran-Toro, Juan-David; Portillo-Rosero, Luz-Mery; Realpe-Realpe, Lina Maria; Urrego-Otero, Katherine (Revista de Ciencias Agrícolas, 2021)
Nematodes of Globodera genus are considered one of the most important and limiting pests for potato crops, since these pathogens are difficult to control and cause losses between 20 and 50% of production. The study was carried out in areas of Túquerres and Contadero, belonging to the department of Nariño, Colombia, where cysts were collected by taking soil samples and obtaining immature females after observing the potato plants roots. Photographic records of symptoms corresponding to the nematode presence during the phenological development of the crop were also taken. This study was carried out in order to determine the present specie in the mentioned areas by studying morphological characters such as: nodules shape of the stylet, stretch marks between the vulva and anus and the female color change towards the cyst formation and relate the biological cycle of the pathogen with the host. Cysts viability tests were carried out, obtaining active larvae in J2 state. The evaluated results corresponded to Globodera pallida species and no evidence Globodera rostochiensis was found in samples. Refering to symptoms observed in field, there was chlorosis, yellowish spots on the foliage and plants with little growth. The appearance of immature females coincides with the phenological stage of flowering, which occurs 90 days after the plant emergence.